Lengthwise Fracture Study of Transversely Inhomogeneous Rods - RIZOV, Victor Iliev (Engineering Transactions, 2020)
A lengthwise crack in a rod that exhibits smooth (continuous) material inhomogeneity in the transverse direction is studied. The rod has a circular cross-section. The lengthwise crack is located arbitrarily along the thickness of the rod. A solution to the strain energy release rate is derived assuming that the moduli of elasticity in tension and compression are distributed continuously in the transverse direction. The strain energy release rate is also analyzed by applying the compliance method for verification. The influences of various factors such as the crack location, material inhomogeneity and the different mechanical behavior of the material in tension and compression on the fracture are investigated and discussed in detail.